Hyperspectral fluorescence lifetime fibre probe spectroscopy for use in the study and diagnosis of osteoarthritis and skin cancer - Thompson,A; Manning,H; Brydegaard,M; Coda,S; Kennedy,G; Patalay,R; Waitong-Braemming,U; De,Beule P; Neil,M; Andersson-Engels,S; Itoh,Y; Bendsøe,N; et al. (Society of Photo-optical Instrumentation Engineers (SPIE), 2011)
We present the application of two fibre-optic-coupled time-resolved spectrofluorometers and a compact steady-state diffuse reflected light/fluorescence spectrometer to in vivo and ex vivo studies of skin cancer and osteoarthritis. In a clinical study of skin cancer, 27 lesions on 25 patients were investigated in vivo before surgical excision of the region measured. Preliminary analysis reveals a statistically significant decrease in the autofluorescence lifetime of basal cell carcinomas compared to neighbouring healthy tissue. A study of autofluorescence signals associated with the onset of osteoarthritis indicates autofluorescence lifetime changes associated with collagen degradation.